100 Years of Recessions: Lessons Learned, but not Applied - Kyle Patterson; Kyle Neumann; James Ondracek; Mohammad Saeed; Andy Bertsch (Bina Nusantara University, 2022)
Large financial institutions, sometimes described as “too big to fail” (TBTF), are the epicenter of economic recessions through the past century. While literature has narrowed a set of causes for major recessions, such as in the Great Recession, fewer attempts have been identified to place each event in context as a series. By comparing causes, treatments, and outcomes of major recessions through the past century with a global perspective, beginning with the Great Depression and ending with the COVID-19 Recession, trends in governmental policy emerge as a framework in which recessions occur and are addressed. The use of fiscal relief packages, or “bailouts,” and deregulation of mergers, acquisitions, and derivative swaps are assessed as factors in the expansion of the TBTF mentality.